Activation of a gamma–cyclodextrin–based metal–organic framework using supercritical carbon dioxide for high–efficient delivery of honokiol. (1st May 2020) - He, Yuanzhi; Hou, Xuefeng; Guo, Jingwen; He, Zehui; Guo, Teng; Liu, Ying; Zhang, Yongtai; Zhang, Jiwen; Feng, Nianping
Highlights: CD-MOF was successfully activated with high surface area and large pore volume by scCO2 processing. Honokiol was introduced into the pores of CD-MOF with high cargo loading by scCO2 -assisted impregnation. Enhanced cellular uptake and increased drug transport across intestinal epithelial cells had been realized by HNK@CD-MOF. HNK@CD-MOF enhanced the oral absorption and bioavailability of honokiol when compared with the cyclodextrin inclusion complex. Abstract: A facile method for the activation of γ-cyclodextrin metal-organic framework (CD-MOF) without channel blockage and framework collapse was first developed using supercritical carbon dioxide (scCO2 ), which enabled higher surface area and larger pore volume. The scCO2 -assisted impregnation method was also applied to introduce the insoluble drug, honokiol (HNK), into the pores of CD-MOF with higher cargo loading compared to the conventional liquid phase incorporation in ethanol. Notably, the resulting HNK-loaded CD-MOF (HNK@CD-MOF) had improved apparent solubility and enhanced dissolution rate. The intestinal cellular uptake and transport experiments demonstrated that CD-MOF could enhance cellular uptake and increase drug transport across the intestinal epithelial cells compared to the cyclodextrin inclusion complex. Moreover, the in vivo pharmacokinetic studies further confirmed that CD-MOF could significantly improve the oral absorption and bioavailability of HNK. Overall, the scCO2 activation and scCO2 -assisted impregnation approaches were demonstrated as promising strategies to maximize the potential capability of CD-MOF.